2012
DOI: 10.1016/j.socnet.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Who are the objects of positive and negative gossip at work?

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
222
1
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(254 citation statements)
references
References 71 publications
(110 reference statements)
7
222
1
10
Order By: Relevance
“…Negative ties (such as interpersonal dislike or conflict) could play a very important role in pushing individuals out of the organization (Labianca & Brass, 2006). Recently, a social network perspective has been applied to positive and negative gossip in organizations (Ellwardt, Labianca, & Wittek, 2012;Grosser, LopezKidwell, & Labianca, 2010), and these studies suggest that particular individuals, including those who are socially isolated, might be targeted for negative gossip by other employees, which might increase turnover intentions. Building on these perspectives by examining the targets of negative gossip and the social structures within which they are embedded could also provide new insights into employees' turnover intentions.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Negative ties (such as interpersonal dislike or conflict) could play a very important role in pushing individuals out of the organization (Labianca & Brass, 2006). Recently, a social network perspective has been applied to positive and negative gossip in organizations (Ellwardt, Labianca, & Wittek, 2012;Grosser, LopezKidwell, & Labianca, 2010), and these studies suggest that particular individuals, including those who are socially isolated, might be targeted for negative gossip by other employees, which might increase turnover intentions. Building on these perspectives by examining the targets of negative gossip and the social structures within which they are embedded could also provide new insights into employees' turnover intentions.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Some norms are clearly unjustified. Ellwardt et al (2012) found that negative gossip often targets those "of low informal status." Gossip becomes clearly impermissible when it serves to reinforce an unjust social order.…”
Section: Limits Of Gossipmentioning
confidence: 99%
“…However, production deviance is justifiable deviant conduct. With the consent of the organization, this behavior is allowed to enable employees to rejuvenate and continue their commitment (DodigCrnkovic & Anokhina, 2008;Ellwardt, Labianca, & Wittek, 2012).…”
Section: Deviant Behaviormentioning
confidence: 99%
“…The behavior also facilitates friendship when employees search information about others, personal exchanges, and social bonds. However, if the gossip is negatively spread, it will affect relationship and communication at work (Ellwardt, Labianca & Wittek, 2012;Ellwardt, Steglich, & Wittek, 2012).…”
Section: The Occurrence Of Deviant Behaviormentioning
confidence: 99%